Smart Location Alarm on Mobile Platform - Lai, Jia Yong (2020)
Travelling to a place to do something is what most people had experienced. Many people have to work, attend formal meetings or regular events in different places, date and time. With Smart Location Alarm application, it allows the users to mark down the places where the users need to be reminded. Thus, they have lower chances to miss their destinations while driving or taking public transportation. The users can inform their friends by using the application without messaging them manually, once they are reaching the marked places. For daily usage, the users can select their favourite weekdays to trigger the location alarms. Besides, the users can also choose a date and time to schedule the time alarms. With Kanban development methodology, the project had proceeded smoothly and well-organized. Tasks had scheduled and executed on time, which increased the efficiency in the development process. As a result, the application reached the deployment stage and it is available for Android users. Due to some limitations, iOS users are not able to use the application. In short, Smart Location Alarm is a tool that improves convenience and reduces burden for human memory.